Injured tubule derived CCN1 exacerbates renal congestion-mediated acute kidney injury and fibrosis - Atsushi Minamida; Tomohiro Nakata; Ryo Kurose; Shinji Sawai; Masashi Nakamura; Minato Umehara; Hiroko Yamauchi-Sawada; Yasuto Sunahara; Yayoi Matoba; Natsuko Okuno-Ozeki; Itaru Nakamura; Kunihiro Nakai; et al. (Scientific Reports)
Abstract Epidemiological studies show that heart failure often leads to kidney dysfunction, known as cardio-renal syndrome (CRS). Elevated central venous pressure, rather than low cardiac output, strongly correlates with worsening renal function and is increasingly recognized as the cause of CRS. However, the molecular mechanisms behind congestion-mediated worsening of kidney injury remain unclear due to the lack of suitable animal models. Here, we used a novel mouse model of renal congestion and identified injured tubule-specific cell-cell interactions in congested kidneys. We found that Cellular Communication Network Factor 1 (CCN1) played a critical role in this process. Transcriptomic analysis of kidneys with ischemia-reperfusion injury (IRI) and renal congestion showed the upregulation of paracrine chemokine-related pathways. CCN1 was upregulated in the acute phase following kidney injury with renal congestion, and phosphorylated focal adhesion kinase (pFAK), a downstream molecule of CCN1, was present in fibroblasts at injury sites. CCN1 activated FAK, promoting fibroblast and macrophage migration. We further examined the effects of CCN1 deletion in tubular epithelia and found that it reduced pFAK expression and alleviated tissue fibrosis. In conclusion, CCN1 plays a key role in fibroblast migration in congestion-mediated worsening of kidney injury and is a potential therapeutic target to prevent fibrosis.